Leadership Based on Role Playing in Class V SDN 90 Sipatana Indonesian - Aini Khoifah; Bachtiar Amrullah Dumbela; Nurul Miftah Sugeha; Rahmatia Talango; Abdul Rahmat; Rusmin Husain (Zien Journals, 2022)
Social skills are very important for children because during school time peer relations so that children can learn to socialize. The purpose of this study is to determine student leadership through role playing. In this study, data collection was carried out through observation, observation, teacher interviews, teaching experiments. The purpose of applying this role playing method is to foster the character of leaders in elementary school children to gain the ability to solve their own problems. And in forming superior character, training students' soul leadership can also train students' self-confidence. By playing the role of social skills can be obtained, students can develop and carry out social relations well and improve social skills
Keywords: Leadership; role playing; social; students